2008
DOI: 10.1177/0091270008322176
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Amlodipine and Olmesartan After Administration of Amlodipine Besylate and Olmesartan Medoxomil in Separate Dosage Forms and as a Fixed‐Dose Combination

Abstract: The pharmacokinetics of amlodipine and olmesartan in healthy volunteers after coadministration of amlodipine besylate and olmesartan medoxomil concomitantly as separate dosage forms and together in a fixed-dose combination tablet were characterized in 5 phase I, randomized, crossover studies. The mean steady-state pharmacokinetics of amlodipine and olmesartan were similar when olmesartan medoxomil 40 mg/day and amlodipine 10 mg/day were administered separately or concomitantly for 10 days. The total and maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
(43 reference statements)
2
21
0
Order By: Relevance
“…No significant pharmacokinetic drug–drug interactions occur when olmesartan medoxomil and amlodipine are co-administered in separate dosage forms 28,29. When orally administered as a fixed-dose combination, amlodipine/olmesartan medoxomil is bioequivalent to single-entity dosage forms of both drugs 28…”
Section: Amlodipine/olmesartan Medoxomil: Pharmacokinetics and Mechanmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant pharmacokinetic drug–drug interactions occur when olmesartan medoxomil and amlodipine are co-administered in separate dosage forms 28,29. When orally administered as a fixed-dose combination, amlodipine/olmesartan medoxomil is bioequivalent to single-entity dosage forms of both drugs 28…”
Section: Amlodipine/olmesartan Medoxomil: Pharmacokinetics and Mechanmentioning
confidence: 99%
“…28 For example, following a single dose of the combination tablet, peak plasma concentrations of amlodipine and olmesartan were 7.6 and 833.3 ng/mL, and values for the area under the plasma concentration-time curve were 424.8 and 5,374.2 ng·h/mL, respectively 28. Corresponding values following administration of amlodipine 10 mg and olmesartan medoxomil 40 mg as two separate dosage forms were 7.4 and 810.3 ng/mL and 410.9 and 5,418.6 ng·h/mL, respectively 28…”
Section: Amlodipine/olmesartan Medoxomil: Pharmacokinetics and Mechanmentioning
confidence: 99%
“…Like other dihydropyridine CCB, amlodipine selectively inhibits calcium (Ca 2+ ) influx across cell membranes in cardiac and vascular smooth muscle with a greater effect on the latter 15. Rohatagi et al16 reported the pharmacokinetics of olmesartan medoxomil and amlodipine besylate alone and in a fixed-dose combination in five phase I crossover studies in healthy volunteers. The similarity of the mean steady-state pharmacokinetics of olmesartan and amlodipine at doses of 40 and 10 mg, respectively, their drug concentration–time curves, and the maximum observed plasma drug concentrations within their prespecified bioequivalence (80%–125%) showed that they were well suited to coadministration in a fixed-dose combination 16.…”
Section: Pharmacodynamics Of Olmesartan and Amlodipinementioning
confidence: 99%
“…Rohatagi et al16 reported the pharmacokinetics of olmesartan medoxomil and amlodipine besylate alone and in a fixed-dose combination in five phase I crossover studies in healthy volunteers. The similarity of the mean steady-state pharmacokinetics of olmesartan and amlodipine at doses of 40 and 10 mg, respectively, their drug concentration–time curves, and the maximum observed plasma drug concentrations within their prespecified bioequivalence (80%–125%) showed that they were well suited to coadministration in a fixed-dose combination 16. Furthermore, coadministration of amlodipine besylate and olmesartan medoxomil, as commercially available separate dosage forms, for 10 days showed no evidence of any negative pharmacokinetic drug–drug interactions 16…”
Section: Pharmacodynamics Of Olmesartan and Amlodipinementioning
confidence: 99%
“…The plasma elimination half-life of Levamlodipine has been found to be 31 ± 13 hrs. Different methods for the determination of Amlodipine in biological fluids, such as gas chromatography (GC) [1] or liquid chromatography (LC) [2][3][4] or mass spectrometric analysis [5][6][7], previously reported methods [8][9][10][11][12] either had long retention time (10-15min) or suffered from low sensitivity and in some cases required large sample injection volumes. Hence the main objective of this work was to develop a simple, sensitive, rapid and reliable mass spectrometry method for the quantification of S-amlodipine in human plasma.…”
Section: Introductionmentioning
confidence: 99%